You Only Have to Wish High Enough – Gifts in Hanif Kureishi’s Gabriel’s Gift - Petr Chalupský (American and British Studies Annual, 2009)
Hanif Kureishi, whose works frequently explore the psychology and intimate life of his predominantly male protagonists, is one of the most acclaimed contemporary British writers of multiethnic origin. This article deals with his fourth novel, Gabriel’s Gift (2001), which, to a certain degree, reassumes the thematic tradition of his earliest works, namely his first novel, The Buddha of Suburbia (1990). It attempts to show that Gabriel’s Gift can be read as a kind of sequel to its more acknowledged predecessor, though its main focus has shifted from racial and political issues to a more private, and also more light-hearted, exploration of the state of humanity. The last section focuses on one of the central characteristics of Kureishi’s oeuvre, his celebration of London as a city of countless opportunities and a positive social and cultural diversity.